Proposed programme for monitoring the Kenya Livestock Development Project - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Outline of objectives of the Kenya Livestock Development Project, expectations of the Government, donors and ILCA from project monitoring, conceptual approach to data collection, and ILCA's role in data collecting and analysis.